Christmas at the Amish bakeshop - Gray, Shelley Shepard (Kensington Publishing Corp., 2021)
As the most joyful holiday draws near, three couples discover the recipe for love includes faith, hope, and the sweetest blessings . . .A CHRISTMAS CAKE FOR REBECCA [by] Shelley Shepard Gray: When carpenter Aden returns to Lancaster after twenty years away, bakeshop owner Rebecca is dismayed to find he's still as handsome and kind as ever. He broke her heart when he left the community back then. Will a holiday emergency provide a second chance at love, this time forever? BEST CHRISTMAS PRESENT EVER [by] Rachel J. Good: When a lonely widower with a sick daughter and a new cake decorator meet at the bakeshop, they discover they were once childhood playmates. But as each of them helps the other care for family, their neighborly kindness inspires a gift that only love could make possible . . . THE CHRISTMAS CUPCAKE [by] Loree Lough: A builder who never learned to read believes he must hide his fond feelings for a kind schoolteacher. But after they run into each other at the bakeshop, she offers to teach him- and as Christmas approaches, each of them learns a lesson about the great gift of love . . .